The effect of heat transfer on the efficiency of binary mixture separation in the method of countercurrent fractional crystallization - V. M. Myasoedenkov; G. A. Nosov; E. M. Khaibulina (Тонкие химические технологии, 2009)
The analysis of heat transfer influence on the efficiency of separation in the countercurrent fractional crystallization process was performed. Using a binary mixture as an example, it has been demonstrated that considering the influence of heat transfer on the separation results in decrease of the height of zone of the mass transfer in the countercurrent crystallization apparatus.